Environmental Accounting Education and Entrepreneurial Character in the Green Economy - masradin masradin (Electronic Journal of Education, Social Economics and Technology, 2026)
This study focuses on analyzing the impact of environmental accounting education on the green economy, character development, and entrepreneurship among college students, and examines how the green economy and character development function as a bridge. The high carbon emissions caused by business actors due to minimal environmental awareness, so universities have a role in the need for entrepreneurs, while universities have a role in developing entrepreneurs who understand environmentally friendly businesses. The research objects were taken from 366 students. The results showed that environmental accounting education had a positive and significant effect on the green economy and character building, but not significantly on students' entrepreneurial intentions. Understanding the green economy was proven to be able to significantly mediate environmental accounting education and students' entrepreneurial intentions, while character building did not play a mediating effect. The conclusion of this study indicates that universities implementing environmentally focused curricula help raise students' awareness of sustainable entrepreneurship. Based on this research, universities should continue integrating curricula with other disciplines and developing real-life entrepreneurial projects to produce entrepreneurs with character and an understanding of the fundamentals of a green economy.